Quality Differentiation and Optimal Pricing Strategy in Multi-Sided Markets - Soo Jin Kim; Pallavi Pal (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper analyzes the generalized quality differentiation model in multi-sided markets with positive externalities, which leads to new insights into the optimal pricing structure of the firm. We find that quality differentiation for users on one side affects not only the side involving differentiation but also the other side due to cross-side network externalities, thereby affecting the pricing structure of multi-sided firms. In addition, quality differentiation affects the strategic relationships among all the choice variables for the platform, enabling the platform to strategically use quality differentiation to raise its profits.
Keywords: D43; L11; L42; 330; multi-sided market; quality differentiation; platform business strategies